ANALISIS AKAR PEMBEDA REKSADANA KONVENSIONAL DAN SYARI’AH - Nurudin, Irfan (LIPI, 2016)
AbstractReksadana is a means of investment that has the main purpose to help and the mobilization of small investors and individuals who invest in the capital market. Indonesia is a country with a majority Muslim population. Most Muslims want the presence of investment instruments in accordance with the Islamic Sharia. Intellectual effort and established the community in the running of his investment, the need for a clear distinction between Islamic and conventional reksana. Research methods in this study is the empirical legal research or sociology, and the approach used is a normative approach. Source data required primary and secondary data is data with the use of the law. The method used is the deductive method of thought thinking and performed an analysis of qualitative analysis.The basic principle of a difference between a conventional reksadana and Islamic reksadana lie in investment objectives, operations, again, surveillance, and contract transactions. This has been the emphasis in Islam run reksadana, but not conventional reksadana accommodate things of concern to reksadana.